Jigsaw Puzzle Therapy to Support Cognitive Function in an Older Adult: A Case Study from Griya Lansia Ciparay - Novika Putri Ismayanti; Sheizi Prista Sari; Raini Diah Susanti (Universitas Tribhuwana Tunggadewi, 2026)
Cognitive decline is a common health problem experienced by older adults and can affect their independence and quality of life. This issue is also aligned with the Sustainable Development Goals (SDG 3: Good Health and Well-Being), which highlight the importance of improving health and well-being across all age groups. Non-pharmacological cognitive stimulation, such as Jigsaw Puzzle Therapy (JPT), is one of the interventions that aims to help maintain brain function. Objective: To describe the implementation and outcomes of Jigsaw Puzzle Therapy (JPT) in an older adult with cognitive impairment at Griya Lansia Ciparay. This case report employed the nursing care process approach involving a 74-year-old female older adult. Cognitive function was assessed before and after the intervention. JPT was administered daily for seven consecutive days using picture-based puzzles with a low level of difficulty. An improvement in cognitive ability was observed, indicated by an increase in cognitive function scores from 15 to 20 after the intervention. The most notable improvements were seen in time and place orientation as well as basic calculation skills. This case report shows that seven sessions of Jigsaw Puzzle Therapy were associated with improvements in the client’s cognitive scores. JPT may serve as a simple and feasible activity to provide cognitive stimulation for older adults in long-term care settings.